Filosofiâ prava v Respublike Belarusʹ: v poiskah balansa - Liapeshka, Barys (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The philosophical and legal studies in the Republic of Belarus are analyzed in the article. The point of view that the tradition of studying of philosophy of law in the Western Europe and in the post-Soviet countries differ greatly is expressed and proved. Attention is drawn to the subject matter of philosophy of law and its principles; controversial aspects of this segment of philosophical and legal knowledge are analyzed. The connection between philosophical and legal problems with the objectives of accomplishment of legal culture is presented. Philosophical and legal issues, which are relevant and described in the works of Belarusian and Russian scientists are studied.
Keywords: philosophy of law; theory of law; Belarus; post-Soviet country; post-totalitarian country